Spatial palaeoecology of large-herbivore hominin prey-species at Salzgitter-Lebenstedt, Lower Saxony, Germany: multi-isotope analysis of sequentially-sampled tooth enamel from Rangifer tarandus and Equus sp. - Heddell-Stevens, Phoebe; Barakat, Sarah; Pastoors, Andreas; Lucas, Mary; Scott, Erin; Le Roux, Petrus; Roberts, Patrick (Frontiers in Environmental Archaeology, 2024)
The application of high-resolution methods to reconstruct the ecology and behavior of large-herbivores within Late Pleistocene contexts in Europe has revealed increasing evidence for variability in diet, habitat preference, ranges and mobility patterns through time and space. This data has major implications for interpretations of hominin subsistence strategies in terms of prey-species selection, which rest to a large extent, on the spatial ecology of these animals and their resulting availability in the environment. To this end, multi-isotope analysis of faunal remains from archaeological sites has been shown to provide direct information in herbivore movements and ranges that move beyond assumptions of consistency in animal behavior through time. The Middle Paleolithic site of Salzgitter-Lebenstedt, Northern Germany, has been put forward as a prime example of specialized hunting of a single taxon – reindeer – by Neanderthals. However, questions remain around the number and season of hunting events. Here we employ strontium (87Sr/86Sr) isotope analysis in combination with stable oxygen (δ18O) and carbon (δ13C) isotope analysis of sequentially-sampled tooth enamel from reindeer (Rangifer tarandus) and horse (Equus sp.) to reconstruct the sub-annual dietary and ranging behaviors of these prey-species at Salzgitter. We find that reindeer exhibit parallel seasonal shifts in diet and likely experienced similar environmental conditions. While the majority of the reindeer display the potential for long-distance climate-induced migrations, mobility patterns and seasonal ranges appear to have differed between individuals. This may be indicative of behavioral flexibility, particularly in migratory behavior of reindeer, during this period in Northern Germany. Horses analyzed here likely consumed a graze-based diet year-round, while potentially undertaking more residential movements on a seasonal basis. We briefly discuss potential implications of these findings on Neanderthal hunting strategies at the site. Finally, we discuss the challenges to the application of 87Sr/86Sr as a provenancing tool in Central Europe, and the importance of multi-isotope approaches and development of additional spatial proxies.